CORRELATION ANALYSIS OF BASIC ENGLISH PROFICIENCY TO TOEFL SCORE OF STUDENTS AT COLLEGE OF HEALTH SCIENCES IN SEMARANG - Ade Kristianus Kaloeti (Suluh Adiluhung Publisher (SAPub), 2024)
This study aims to identify the correlation between basic English proficiency and the acquisition of TOEFL scores by 6th semester students at STIKES Telogorejo Semarang. This study used descriptive quantitative method. The population in this study were 6th semester students of STIKES Telogorejo Semarang with a sample of 179 respondents. Data collection techniques are test techniques and questionnaire techniques. The data were analyzed using the Spearman correlation test with the help of the SPSS for Windows version 25.0 program. The test results showed that as many as 83.3% of students scored below the minimum standard of 450. Based on the Spearman correlation test, there is a significant correlation at a low level between listening skills, grammar skills and ability to understand reading texts with TOEFL score results. The positive direction of the correlation indicates that TOEFL score results increase if basic skills in English also increase.